Allaeotes niger, a weevil introduced to Cuba and the only known New World Stromboscerini (Coleoptera: Curculionidae: Dryophthorinae) - Grebennikov, Vasily V. (Zootaxa, 2020)
Allaeotes niger He, Zhang and Pelsue, a weevil hitherto known only from the type series collected in China, is for the first time reported from Cuba. In addition to three historical Cuban specimens, approximately one hundred adults were observed in 2018 under bark of fallen logs at a plantation of (likely non-native) pines in westernmost Pinar del Río province. This is the only New World record of a member of the monophyletic core of the tribe Stromboscerini, otherwise distributed in a triangle delimited by Japan, Sri Lanka and northern Australia (plus a single mysterious record from Uganda). Phylogenetic analysis of one mitochondrial (COI) and two nuclear (ITS2 and 28S) markers recovered the Cuban specimens nested within the tribe, but not in a clade with two unnamed congeners from Vietnam. Adults of all four known Allaeotes species are illustrated, including both named ones. Remarkably, both Cuban and Ugandan records of extraterritorial Stromboscerini pertain to species associated with dead wood, a biological trait possibly facilitating human-assisted transoceanic dispersal. Cuban populations of A. niger are interpreted as a pre-1990 human-mediated introduction. Two additional specimens of A. niger intercepted at US ports of entry arriving from China and the Dominican Republic, respectively, corroborate this hypothesis and suggest China as a likely origin of the Cuban introduction. All data used herein (specimen images, geographical localities, DNA sequences) are available online in a public dataset dx.doi.org/10.5883/DS-VGDS012.